2015
DOI: 10.1080/10610278.2015.1034126
|View full text |Cite
|
Sign up to set email alerts
|

Anion transport and binding properties of N N′-(phenylmethylene)dibenzamide based receptors

Abstract: Dedicated to friend and mentor Professor Jonathan L. Sessler on the occasion of his 60th birthday.The anion transport and binding properties of a series of bis-amide based compounds have been studied in POPC lipid bilayers. The compounds display evidence of aggregation in solution with single crystal X-ray crystallographic analysis showing hydrogen bonding between the amide substituents of adjacent receptors in the solid state.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…have shown that they exchange Cl -/NO 3 better than Cl -/HCO 3 and both are worse than the corresponding values obtained for bis(ureas). 79 Jeong et al have demonstrated that bis(ureas) based on cis-or trans-amide linkage display really different ionophoric activity as a function on the amide conformation. Trans-amide conformation is nearly no active.…”
Section: )mentioning
confidence: 99%
“…have shown that they exchange Cl -/NO 3 better than Cl -/HCO 3 and both are worse than the corresponding values obtained for bis(ureas). 79 Jeong et al have demonstrated that bis(ureas) based on cis-or trans-amide linkage display really different ionophoric activity as a function on the amide conformation. Trans-amide conformation is nearly no active.…”
Section: )mentioning
confidence: 99%